2018
DOI: 10.1016/j.phrs.2018.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-12 as an endogenous resolution promoting factor following myocardial infarction

Abstract: Following myocardial infarction (MI), timely resolution of inflammation promotes wound healing and scar formation while limiting excessive tissue damage. Resolution promoting factors (RPFs) are agents that blunt leukocyte trafficking and inflammation, promote necrotic and apoptotic cell clearance, and stimulate scar formation. Previously identified RPFs include mediators derived from lipids (resolvins, lipoxins, protectins, and maresins), proteins (glucocorticoids, annexin A1, galectin 1, and melanocortins), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 100 publications
(112 reference statements)
0
9
0
Order By: Relevance
“…The Mϕ-specific matrix metalloproteinase, i.e., MMP12, is identified as an endogenous resolution promoting factor in the events of myocardial infarction ( 30 ), and it plays a protective role by arresting inflammatory pathways and neutrophil infiltration in various diseases ( 31 ). MMP13 is a member of the collagenase family, which degrades many types of collagens and other profibrotic molecules ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Mϕ-specific matrix metalloproteinase, i.e., MMP12, is identified as an endogenous resolution promoting factor in the events of myocardial infarction ( 30 ), and it plays a protective role by arresting inflammatory pathways and neutrophil infiltration in various diseases ( 31 ). MMP13 is a member of the collagenase family, which degrades many types of collagens and other profibrotic molecules ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, among the top-20 DEGs, there were a number of DEGs identified in the transcriptome of chronic in vivo NVUs related to inflammation. We identified Crtam , which determines the CD4 + cytotoxic T-lymphocyte lineage [66], Ngp , which functions as a cytokine expressed from CD4 + helper T-cells, and Mmp12 , which is an important regulator of leukocyte trafficking, cytokine secretion and T-helper cell differentiation [41]. Our previous study has shown that B-cell depletion reduces the maturation of CCM lesion in the mouse model [63].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged lifespan of neutrophils under the influence of tumor necrosis factor (TNF) and IL-1β was associated with increased endothelial damage and adverse myocardial healing ( 42 ), while matrix metalloproteinase (MMP)-12 seems to favor neutrophilic apoptosis ( 17 ). Overall, MMP-12 has been shown to possess potent pro-resolving properties, influencing inflammatory signaling and controlling cellular clearance, and neutrophils appeared to be the source of MMP-12 themselves ( 43 ).…”
Section: Neutrophilsmentioning
confidence: 99%